2014
DOI: 10.1161/strokeaha.114.005464
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor and Erythropoietin Infusion Accelerate Functional Recovery in Combination With Rehabilitation

Abstract: Sixty-seven male Sprague-Dawley rats were matched for poststroke grasping/retrieving performance on the staircase test and randomized into 4 groups: rehabilitation+EGF/erythropoietin (n=13), rehabilitation+artificial cerebrospinal fluid (aCSF; n=12), no rehabilitation+EGF/erythropoietin (n=12), and no rehabilitation+aCSF (n=13). All procedures were approved by the Memorial University Animal Care Committee and comply with regulations set by the Canadian Council of Animal Care (see detailed Methods in the online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…This concept is underscored by recent evidence that further combination of reaching+enrichment with application of neuroplasticity-promoting factors accelerates the rate of recovery beyond what is possible with only reachi ng+enrichment. 6,25,30 The secondary objective of the study was to assess the generalizability of a recent predictive model of stroke recovery across rodent forelimb grasping tasks. Previously, we demonstrated that rehabilitation intensity, cortical infarct volume, and initial poststroke impairment could be used to predict the final level of forelimb recovery in the Montoya staircase task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept is underscored by recent evidence that further combination of reaching+enrichment with application of neuroplasticity-promoting factors accelerates the rate of recovery beyond what is possible with only reachi ng+enrichment. 6,25,30 The secondary objective of the study was to assess the generalizability of a recent predictive model of stroke recovery across rodent forelimb grasping tasks. Previously, we demonstrated that rehabilitation intensity, cortical infarct volume, and initial poststroke impairment could be used to predict the final level of forelimb recovery in the Montoya staircase task.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous rodent focal ischemia experiments indicate that environmental enrichment in combination with intensive taskspecific rehabilitation (ie, reach training) promotes recovery of both task-specific (ie, staircase/single pellet) and generalized motor functions (ie, beam walking/cylinder). [4][5][6] Surprisingly, despite the efficacy of this rehabilitation strategy, the respective contribution of each of these components to functional recovery has not been directly compared.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40 In two studies by Biernaskie and Corbett, 40 after stereotaxic microinjection of ET-1 to the distal portion of the middle cerebral artery, recovery to~50% of prestroke ability on the Montoya staircase test was shown by 40 days after ischemic insult with enriched rehabilitation therapy initiated within the first week after stroke. Jeffers et al 24 in turn reported that after 2 weeks of epidermal growth factor and erythropoietin infusion into the ipsilateral ventricle and an additional 2 weeks of enriched rehabilitation therapy, animals recovered to~55% of their prestroke performance; and further on, at 10 weeks after stroke, reached~60% of their prestroke performance level. Of note, however, Biernaskie et al and Jeffers et al observed more severe deficits in skilled reaching ability 1 week after ischemic insult (~20% and~25% of prestroke performance, respectively) than those observed in the present study (~34% of prestroke performance).…”
Section: ) (A)mentioning
confidence: 99%
“…After stroke, skilled use of the affected hand (or paw) is highly resistant to recovery in both humans and animals. In rats, enriched rehabilitation produces substantial improvements in the recovery of skilled reaching [25,34,35,36,67]. The protocol consists of enriched housing ( a ) and/or running exercise ( b ) in combination with several hours of daily reach training ( c ) of the impaired limb.…”
Section: Enriched Rehabilitation and Stroke Recoverymentioning
confidence: 99%